2018
DOI: 10.1101/350710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Teachers’ approaches to genetics teaching mirror their choice of content and avoidance of sensitive issues

Abstract: The skills required to understand genetic phenomena and transfer knowledge to real world situations are an important part of 21st century scientific literacy. While socio-scientific issues (SSI) are increasingly emphasised in science curricula, teachers have low interest in adopting SSI in teaching. Little is known about how teachers choose content for their teaching, although this process translates curricula to teaching practice. We explored how teachers choose content and contexts for biology courses on cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This is significantly different from traditional science classes where scientific knowledge is the focus, and it is obviously challenging for science teachers to consider these multiple subject areas. This is why previous studies reported that teachers lacked confidence in handling controversial issues (Bryce & Gray, 2004;Hofstein et al, 2011) or lacked knowledge and teaching strategies (Aivelo & Uitto, 2019;Borgerding & Dagistan, 2018;Carson & Dawson, 2016;Ozturk & Bozkurt Altan, 2019). Even though teachers encountered the aforementioned difficulties, similar results from studies conducted with preservice teachers were also reported (see Genel & Topcu, 2016;Kara, 2012).…”
Section: Pre-service Teachers' Use Of Multiple Subject Areas In Decision-makingmentioning
confidence: 82%
See 2 more Smart Citations
“…This is significantly different from traditional science classes where scientific knowledge is the focus, and it is obviously challenging for science teachers to consider these multiple subject areas. This is why previous studies reported that teachers lacked confidence in handling controversial issues (Bryce & Gray, 2004;Hofstein et al, 2011) or lacked knowledge and teaching strategies (Aivelo & Uitto, 2019;Borgerding & Dagistan, 2018;Carson & Dawson, 2016;Ozturk & Bozkurt Altan, 2019). Even though teachers encountered the aforementioned difficulties, similar results from studies conducted with preservice teachers were also reported (see Genel & Topcu, 2016;Kara, 2012).…”
Section: Pre-service Teachers' Use Of Multiple Subject Areas In Decision-makingmentioning
confidence: 82%
“…While PTs use ethics and morals in their own decisions, this is not reflecting in their teaching of SSI, possibly for the same reasons stated abovecurricular pressure, lack of time, and the pressure of preparing for state exams. Another reason might be that PTs are inexperienced teachers, who, according to the available research, are more open to discussion and more eager to include societal aspects in their classrooms (Aivelo & Uitto, 2019). As the PTs in our study were inexperienced teachers, this might explain their reliance on science and ethics/morality to support their decisions.…”
Section: Pre-service Teachers' Use Of Multiple Subject Areas In Decision-makingmentioning
confidence: 87%
See 1 more Smart Citation
“…The application of TPACK model in learning can assist educators in conveying learning concepts to students, motivate students to learn, provide opportunities for students to be more active in experimenting according to concepts, evaluate, provide feedback on the results of student assignments, and assist students in communicating various solutions (Stoilescu, 2015). Specific strategies on three aspects of knowledge, namely technology, pedagogy, and content are also needed by educators in learning genetics (Aivelo & Uitto, 2018). TPACK model is needed by educators to integrate technology in learning effectively (Koehler et al, 2013;Mishra & Koehler, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature reports many teachers perceived SSI-based teaching as challenging (Sadler, Amirshokoohi, Kazempour, & Allspaw, 2006;Rundgren & Chang Rundgren, 2018). Many teachers were reported to feel uncomfortable introducing ethics and values along with scientific content , to have lack of knowledge (Aivelo & Uitto, 2019), and lack of confidence for dealing with SSI (Bryce & Gray, 2004).…”
Section: Introductionmentioning
confidence: 99%